Media (translation. a transdisciplinary journal, 2022)
The asymmetries of globalization and the current inequalities in the production of knowledge and information are directly mirrored in translation, and this becomes visible when the directionality of global information flows starts to be questioned. Thus, some accounts of globalization have pointed to the number of book translations from English and into English as an indication of the power distribution in global information flows, where those at the core do the transmission and those at the periphery merely receive it.